Pengaruh Terapi Tertawa Terhadap Tingkat Depresi Pada Lansia Di Upt Panti Wredha Mojopahit Mojokerto - Wicaksono, Arif; Andriyanto, Arief (JURNAL KEPERAWATAN BINA SEHAT, 2015)
The aging process is degenerative that will result in physical changes, cognitive, spiritual and psycho-social.The Changes that emerges is a psychological stressor in the elderly that will result in psychological problems such as depression.The purpose of this study was to determine the effect of laughter therapy on the level of depression in the elderly in nursing homes MojopahitMojokerto.The study design that used here is the pre-experiment with design One-Group Pre-Post Test Design.Overall elderly population who live in the orphanage until 44 become the samples of 24 elderly taken by purposive sampling.The independent variable of laughter therapy and dependent one levels on depression in the elderly.The data were taken using questionnaire that is used before and after laugh therapy.After all the data was collected and statistical test was processed followed by a Wilcoxon sign test SPSS17, the results showed Asymp.Sig value (2-tailed) of 0.014 and α of 0.05.Because Asymp.Sig value (2-tailed) <α 0.05 then H0 is rejected and H1 is accepted, which means there is the effect of laughter therapy on the level of depression in the elderly.In some old depression is a psychological problem that will affect quality of life. Senior citizens are often need to be handling intervention psychological depression. Laughter therapy is an effective therapy because with given therapy laugh citizens can develop ability to communicate and intimacy in relationships with each other to citizens.Keywords:Depression, elderly, laughter therapyThe aging process is degenerative that will result in physical changes, cognitive, spiritual and psycho-social.The Changes that emerges is a psychological stressor in the elderly that will result in psychological problems such as depression.The purpose of this study was to determine the effect of laughter therapy on the level of depression in the elderly in nursing homes MojopahitMojokerto.The study design that used here is the pre-experiment with design One-Group Pre-Post Test Design.Overall elderly population who live in the orphanage until 44 become the samples of 24 elderly taken by purposive sampling.The independent variable of laughter therapy and dependent one levels on depression in the elderly.The data were taken using questionnaire that is used before and after laugh therapy.After all the data was collected and statistical test was processed followed by a Wilcoxon sign test SPSS17, the results showed Asymp.Sig value (2-tailed) of 0.014 and α of 0.05.Because Asymp.Sig value (2-tailed) <α 0.05 then H0 is rejected and H1 is accepted, which means there is the effect of laughter therapy on the level of depression in the elderly.In some old depression is a psychological problem that will affect quality of life. Senior citizens are often need to be handling intervention psychological depression. Laughter therapy is an effective therapy because with given therapy laugh citizens can develop ability to communicate and intimacy in relationships with each other to citizens.